Pendampingan Menggapai Keberkahan Upah Kerja PLTA Ir. H. Djuanda di Kecamatan Jatiluhur Kabupaten Purwakarta - Nuradilah, Ai; Kurnia, Asep Dede; Nurbaeti, Ayi (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
There is a lot of money in the bank but every day the wife argues. Children do not bring happiness even if there are many. With friends and neighbors around there is nothing good. Vehicles are always in trouble. Obedience to Allah is getting weaker day by day. The mind is just the world and the world. Property and possessions. Always look to the deeper things of the world. Never satisfied, even though his mouth sings alhamdulillah every minute. This PKM aims to provide assistance to achieve the blessings of working wages for PLTA Ir. H. Djuanda Jatiluhur, Purwakarta Regency. Implementation of assistance to achieve the blessing of working wages at hydropower plant Ir. H. Djuanda Jatiluhur Purwakarta Regency carried out in 2 ways, namely through a joint study with a lecture system between the presenter and all employees of the Jatiluhur Purwakarta Hydroelectric Power Plant. Furthermore, through joint recitations as one of the efforts to achieve the blessings of work wages and the protection of Allah SWT. In order to avoid wages and sustenance that are not lawful or not blessed.